Analisis Kerentanan Tanah Terhadap Gempa Bumi Menggunakan Metode Horizontal to Vertical Spectral Ratio di Daerah Way Huwi, Lampung Selatan - Angelica Noviani Sitio; Rizki Wulandari; Selvi Misnia Irawati; Dwi Putri Meisya br Sinuhaji (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to evaluate the level of soil seismic vulnerability in Way Huwi Village, South Lampung, using the Horizontal to Vertical Spectral Ratio (HVSR) method. The analysis was conducted based on parameters including natural frequency, soil amplification factor, seismic vulnerability index, and shear-wave velocity to a depth of 30 m (V_S30). The results indicate that the subsurface conditions of the study area are heterogeneous, as reflected by the spatial variation of HVSR parameters across the area. Areas characterized by low natural frequency (f₀ < 5 Hz) and high amplification factor (A₀ > 3.5) are generally associated with thick, unconsolidated soft sediments, resulting in higher seismic vulnerability. In contrast, areas with higher V_S30 values indicate stiffer and more compact soil conditions, leading to a more stable ground response to earthquake shaking. V_S30 estimation using Particle Swarm Optimization (PSO) and Genetic Algorithm (GA) methods produced consistent results, where lower V_S30 values correlate with increased amplification factors and seismic vulnerability indices. Based on these findings, areas with high seismic vulnerability, particularly around measurement points SS2, SS10, and SS22, are recommended as priority zones for earthquake risk mitigation efforts. The results of this study are expected to serve as a basis for spatial planning, earthquake-resistant building design, and disaster risk management in Way Huwi Village.